DIMENSION OF SEXUAL COERCION AGAINST GIRL’S CHILD EDUCATION: ITS IMPLICATIONS ON TERTIARY INSTITUTIONS IN NIGERIA - Yahaya, Abdulrahman (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2023)
The focus of this paper is the “dimension of sexual coercion against girl’s child education: its implications on tertiary Institutions in Nigeria”. In doing so, the paper employs the qualitative methodology for sourcing materials that are related to the topic were survey method adopted, and data were collected through in-depth interviews and complimented with literary materials. Sexual coercion practice is an illegal behavior that has been bedeviling genders more especially girls and women for long period of time silently in some communities without proper condemnation and publicity. It highlights the concept of sexual coercion, its nature, who is girl child, her education in the society including implications of sexual coercion or harassment in tertiary institutions in Nigeria. Finally, the paper concludes by proffering solutions for curbing the menace of this ugly practice for the realization of effective learning of girls and women in tertiary institutions in Nigeria. The study recommended that there was an urgent need for engagement of various stakeholders in Nigeria and beyond, to checkmate the issue of gender in relation to education of the girl child in the society.